Cognitivist Psychology and Arabic Language Instruction: Implications for Curriculum and Classroom Practice - Yuli Imawan; Alimudin Alimudin; Rihanatul Fauziah (Lingu, 2026)
Purpose – This study examines how a cognitivist psychological framework—particularly the theories of Piaget, Bruner, Gagné, and Ausubel—can enrich Arabic language pedagogy by providing a cognitively grounded foundation for instructional design and classroom practice. Design/methods/approach – This research employs a qualitative conceptual approach using systematic document-based analysis. Classical and contemporary literature on cognitive psychology and Arabic language pedagogy was identified, selected, and analyzed through dialectical thematic content analysis. The process involved categorizing major cognitive constructs—such as schema, assimilation, accommodation, information processing, and meaningful learning—mapping their pedagogical relevance, and synthesizing them into an integrated instructional framework. The analysis relied on theoretical triangulation to ensure conceptual rigor and internal coherence. Findings – The study reveals that cognitivist theory offers a comprehensive framework for overcoming mechanistic and behavioristic tendencies in Arabic language instruction. Effective learning is shown to depend on alignment between instructional strategies and learners’ cognitive structures, emphasizing staged development, meaningful integration, and active knowledge construction. The synthesis generates six strategic implications: reorienting objectives toward communicative competence; cultivating a supportive language environment (bi’ah lughawiyyah); optimizing multimodal media use; integrating intercultural competence; organizing content according to developmental readiness; and implementing discovery- and problem-based learning models. These dimensions collectively reposition Arabic pedagogy as a structured process of cognitive engagement rather than rote linguistic transmission. Research Implications – This research calls for the systematic integration of cognitivist principles into Arabic curriculum development and teacher education in order to foster communicative competence, cognitive autonomy, and sustainable meaning-making beyond symbolic memorization.